2001
DOI: 10.1523/jneurosci.21-12-04436.2001
|View full text |Cite
|
Sign up to set email alerts
|

Endomorphin-1: Induction of Motor Behavior and Lack of Receptor Desensitization

Abstract: The endomorphins are recently discovered endogenous agonists for the -opioid receptor (Zadina et al., 1997). Endomorphins produce analgesia; however, their role in other brain functions has not been elucidated. We have investigated the behavioral effects of endomorphin-1 in the globus pallidus, a brain region that is rich in -opioid receptors and involved in motor control. Bilateral administration of endomorphin-1 in the globus pallidus of rats induced orofacial dyskinesia. This effect was dose-dependent and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Our results are consistent with those obtained by Mehta et al (2001), who examined the influence of endomorphins on the activity of basal ganglia, specific subcortical brain structures that play an important role in the control of movement (Delfs et al, 1994;Peckys and Landwehrmeyer, 1999). Dysfunction of the basal ganglia, resulting from specific degeneration of neurons, as in Parkinson's and Huntington's diseases, or from the administration of pharmacological agents, leads to severe motor disorders (Albin et al, 1991;Chesselet and Delfs, 1996).…”
Section: A Biological Effects Of Endomorphinssupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with those obtained by Mehta et al (2001), who examined the influence of endomorphins on the activity of basal ganglia, specific subcortical brain structures that play an important role in the control of movement (Delfs et al, 1994;Peckys and Landwehrmeyer, 1999). Dysfunction of the basal ganglia, resulting from specific degeneration of neurons, as in Parkinson's and Huntington's diseases, or from the administration of pharmacological agents, leads to severe motor disorders (Albin et al, 1991;Chesselet and Delfs, 1996).…”
Section: A Biological Effects Of Endomorphinssupporting
confidence: 91%
“…Within the basal ganglia, a subpopulation of neurons of the globus pallidus expresses particularly high levels of -opioid receptor mRNA (Delfs et al, 1994;Obeso et al, 2000). Morphine injections into the globus pallidus produced a robust increase in locomotor activity (Anagnostakis et al, 1992), whereas endomorphin-1 induced orofacial dyskinesia (Mehta et al, 2001). The authors of that report suggested that stimulation of the locomotor activity by morphine could be mediated by ␦-and -opioid receptors and the inhibitory activity of endomorphin-1 might involve -opioid receptors.…”
Section: A Biological Effects Of Endomorphinsmentioning
confidence: 99%
“…Alternatively, as enkephalin is not selective for δ-opioid receptors, enhanced enkephalin levels might lead to the stimulation of other classes of opioid receptor in GPe and contribute to changes in firing pattern. The recent observation that stimulation of µ-opioid receptors in the rodent homologue of GPe can elicit dyskinesia in rats 105 is in accordance with of this idea.…”
Section: Changes In Non-dopamine Systems In Lidsupporting
confidence: 62%
“…For that purpose, an additional experiment on naloxone, an opioid receptor antagonist that acts at all opioid receptor subtypes, although with a greater affinity for mu-opioid receptors, was included. Naloxone was chosen, because studies on antinociceptive behavior (Stone et al, 1997;Goldberg et al, 1998), motor behavior (Mehta et al, 2001), electrophysiological studies (Chapman et al, 1997;Wang et al, 2000), and systemic blood pressure studies (Czapla et al, 1998;Champion et al, 1997) have revealed that EM-2 and EM-1 produce naloxone-sensitive effects. The pretreatment by naloxone was carried out 20 min before and 10 min before starting the intra-accumbal infusion of the EM-1 or EM-2.…”
Section: Introductionmentioning
confidence: 99%